Thrombotic thrombocytopenic purpura in a patient with snake bite - Murthy, Pooja R; Kumar AK, Ajith; Karanth, Sunil; Kalashetty, Mallikarjun (Indian Journal of Case Reports, 2019)
Snakebite envenomation is a common scenario in southern India. Among the various causes of acquired thrombotic thrombocytopenic purpura (TTP), snake bite envenomation is very rarely reported. We present a rare case of a 51-year-old man with TTP following snakebite envenomation. He developed features of TTP including impaired neurological state, renal dysfunction, low platelets, fever, microangiopathic hemolytic anemia on day 5 following snakebite. He received 7 cycles of plasma exchange and showed remarkable improvement. We are presenting this case to create awareness regarding TTP following snakebite as it has a very significant implication on treatment and mortality.